2017
DOI: 10.18632/oncotarget.14930
|View full text |Cite
|
Sign up to set email alerts
|

microRNA-210-3p depletion by CRISPR/Cas9 promoted tumorigenesis through revival of TWIST1 in renal cell carcinoma

Abstract: Previous studies showed that five miRNAs (miR-885-5p, miR-1274, miR-210-3p, miR-224 and miR-1290) were upregulated the most in clear cell renal cell carcinoma (ccRCC). Our focus was to understand from a clinical standpoint the functional consequences of upregulating miR-210-3p. Towards this, we utilized the CRISPR/Cas9 gene editing system to deplete miR-210-3p in RCC cell lines (786-o, A498 and Caki2) and characterized the outcomes. We observed that miR-210-3p depletion dramatically increased tumorigenesis, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
52
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 44 publications
1
52
0
Order By: Relevance
“…All cell lines were tested and found negative for mycoplasma (e-Myco Mycoplasma PCR Detection Kit; iNtRON, Korea). These cell lines were incubated as previously described (15). Gavage feeding of sunitinib (40 or 25 mg/kg, five times a week; biorbyt, CA, USA) was performed in mice.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…All cell lines were tested and found negative for mycoplasma (e-Myco Mycoplasma PCR Detection Kit; iNtRON, Korea). These cell lines were incubated as previously described (15). Gavage feeding of sunitinib (40 or 25 mg/kg, five times a week; biorbyt, CA, USA) was performed in mice.…”
Section: Methodsmentioning
confidence: 99%
“…Gavage feeding of sunitinib (40 or 25 mg/kg, five times a week; biorbyt, CA, USA) was performed in mice. The tumour sizes and weights were measured and calculated as previously described (15). The chemical structures of sunitinib is in Supplementary Figure 1A.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ding et al found that miR-367 expression was increased in both human ccRCC tissues and cell lines and that ectopic high expression of miR-367 could promote cell proliferation and metastasis by targeting metastasis associated protein 3 (MTA3) in ccRCC [21]. Yoshino H et al reported that miR-210-3p was downregulated in ccRCC, and the deletion of miR-210-3p promoted tumorigenesis through revival of TWIST1 [22].…”
Section: Discussionmentioning
confidence: 99%